The invisibility of young people in family farming: a gender perspective in the semi-arid region of Ceará, Brazil - Rabelo Laudemira Silva; Burte Julien Daniel Pierre; Boillot Élie Anatole Simon; Gasmi Hela; Romão Oliveira Wellington; Fradi Fajr; Rios Mariana Machado; Martins Eduardo S.P.R. (Cahiers Agricultures, 2023)
The evolution of family farming cannot be analyzed only from the perspective of production. Since it is also a kinship unit, the family farm reveals social tensions that contribute to the migration of young people, especially for young women. This study presents an analysis of the factors that contribute to this migratory process, considering youth and gender variables. The analysis is based on a participatory diagnosis, multisectoral interviews and surveys in thirty-three communities located in the center of the Ceará State (Northeastern Brazil). The research reveals that the main factor of this migratory process is the lack of appreciation of family farming by the qualified rural youth, who participate little in decision-making. When the analysis of the migration is gender-focused, the invisibility of young women productive and reproductive work stands out as the main driver of migration to urban areas and proves to be greater than for young men. Rural youth migration will shape the rural territory and will probably change the format of family farming. Understanding its factors may help to propose public policies more adapted for family farming.